Philippine financial almanac II - Litiatco, Vicki Jugo. (Manila Ventures Unlimited, 1999)
An almanac on the numerous and growing financial institutions in the Philippines. Due to the Asian economic crisis, articles from personalities in the financial industry are not included in the almanac. Even then it still provides much information on financial agencies, particularly in the insurance business.
A biannual publication alternately with the Philippine Banking Almanac.
Title from cover.
Keywords: Financial institutions -- Philippines -- Directories; Banks and Banking -- Philippines -- Directories